Lectures on metrices - Wedderburn, J. H. M. (New York Dover publications, 1964)
Lectures on matrices typically cover the fundamental concepts of matrix algebra, including matrix operations, types of matrices, and their properties. These lectures often delve into more advanced topics like linear transformations, eigenvalues, eigenvectors, and applications of matrices in various fields.
Keywords: Algebra mathematics; Linear algebra; Mathematics